P2 / O3 two-phase layered oxide as well as preparation method and application thereof

By adjusting the element ratio and doping elements of the P2/O3 biphase layered oxide material, combined with the advantages of P2 and O3 phases, the limitations of existing sodium ion battery materials in terms of rate performance and energy density are solved, and electrode materials with high specific capacity, long cycle life and excellent rate performance are achieved.

CN119797438APending Publication Date: 2025-04-11SOUTHWEST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510204041.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The P2 and O3 materials of existing sodium ion batteries have limitations in rate performance and energy density, making it difficult to achieve high energy density and long cycle life at the same time.

Method used

Using P2/O3 biphase layered oxide material, electrode materials with high specific capacity, long cycle life and excellent rate performance are prepared by adjusting the element ratio and doping elements, combining the advantages of P2 and O3 phases.

Benefits of technology

It has achieved high specific capacity, long cycle life and excellent rate performance of sodium ion battery positive electrode materials, and is suitable for portable electronic equipment and large-scale energy storage fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797438A_ABST
    Figure CN119797438A_ABST
Patent Text Reader

Abstract

The invention discloses a P2 / O3 biphase layered oxide and a preparation method and application thereof, the chemical formula of the oxide is NaxFeaMnbLicAdO2, a + b + c + d = 1, x is more than 0.5 and less than 1.2, a + b is more than or equal to 0.7, c is more than or equal to 0.005 and less than 0.3, d is more than or equal to 0.005 and less than 0.3, and A is one or more than two of K, Mg and Ca elements. Compared with a single-phase material, the double-phase structure material has high ion diffusivity of a P phase and high Na initial content of an O phase, the phase change degree of the material is reduced, and excellent electrochemical performance is shown. According to the invention, phase content adjustment is carried out in a doping manner, the two-phase sodium ion battery positive electrode material with good cycle performance and excellent rate capability is prepared, the composition elements are all elements rich in the earth, the manufacturing cost is relatively low, and the commercial potential of large-scale production is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sodium ion batteries, and specifically relates to a P2 / O3 two-phase layered oxide and a preparation method thereof and application thereof as a positive electrode material for sodium ion batteries. Background Art

[0002] With the widespread application of batteries in electronic products, electric vehicles and energy storage systems, the market demand for high-performance batteries is steadily growing. However, the manufacture of traditional lithium-ion batteries relies on lithium, a scarce resource that is expensive to mine and extremely unevenly distributed, concentrated in a few countries. This situation has inspired researchers to explore cheaper and more widely distributed alternative technologies. Among the many alternatives, sodium-ion batteries have attracted much attention due to their low raw material cost, high crustal abundance and wide global distribution. As an abundant and environmentally friendly element, sodium is considered a powerful alternative to lithium-ion batteries in the future large-scale energy storage field.

[0003] Sodium ion layered oxides have become a research hotspot due to their structural diversity, designability, and potential anion redox behavior. According to the coordination environment of sodium in the layered structure, layered oxides are mainly divided into P2-type and O3-type materials. Among them, P2-type materials have a large interlayer spacing, which provides a channel for rapid migration of sodium ions, making them excellent in rate performance; however, the energy density of P2 materials is relatively low, which limits their practical application. O3-type materials perform well in initial capacity, but their structure has poor stability in repeated cycles and is prone to irreversible phase changes.

[0004] In order to overcome the single performance limitations of P2 and O3 materials at the same time, P2 / O3 dual-phase cathode materials came into being. This type of material achieves synergy between the two phases by integrating the structural characteristics of P2 and O3. On the one hand, the P2 phase provides good rate performance and structural stability; on the other hand, the high capacity characteristics of the O3 phase can effectively improve the energy density of the material. Therefore, the research and design of P2 / O3 dual-phase materials not only provides a new direction for the development of sodium-ion battery cathodes, but also lays an important foundation for realizing energy storage systems with high energy density and long cycle life.

[0005] In dual-phase materials, it is particularly important to adjust the element selection of the phase and the regulation of the optimal phase ratio. Chinese invention patent CN 116573683B discloses a high-entropy positive electrode material for sodium-ion batteries co-doped with Al, Zn, Ti and Fe. The technical solution uses Zn, Nb, Fe, Co and Cu for high-entropy doping. Chinese invention patent CN 116573683 B discloses a sodium-rich P2 / O3 dual-phase layered oxide and its preparation method, a positive electrode material for sodium-ion batteries and a battery. In the technical solution, Zn element doping is used to adjust the phase ratio. However, the doping elements will affect the capacity or cycle stability.

[0006] Therefore, further optimization of P2 / O3 dual-phase materials is a topic that technicians in this field need to study urgently. Summary of the invention

[0007] In view of this, one of the purposes of the present invention is to provide a P2 / O3 dual-phase layered oxide; the second purpose of the present invention is to provide a method for preparing a P2 / O3 dual-phase layered oxide; the third purpose of the present invention is to provide an application of a P2 / O3 dual-phase layered oxide as a positive electrode material for a sodium ion battery. The P2 / O3 dual-phase layered oxide electrode material provided by the present invention has the characteristics of high specific capacity, long cycle life, and better rate performance.

[0008] The technical solution of the present invention is:

[0009] 1. A P2 / O3 dual-phase layered oxide having a chemical formula of Na x Fe a Mn b Li c A d O2, wherein a+b+c+d=1, 0.5<x<1.2, a+b≥0.7, 0.005≤c<0.3, 0.005≤d<0.3, and A is one or more of K, Mg and Ca elements.

[0010] Preferably, the P2 / O3 dual-phase layered oxide Na x Fe a Mn b Li c A d O2, wherein 0.6<x<0.8, 0.05≤c<0.15, 0.05≤d<0.15.

[0011] Preferably, the P2 / O3 dual-phase layered oxide has a chemical formula of Na x Fe a Mn b Li c Mg dO2.

[0012] 2. A method for preparing a P2 / O3 dual-phase layered oxide, characterized in that it comprises the following steps:

[0013] S1. Take a sodium source compound, an iron source chemical, a manganese source compound, a lithium source compound, and a cation A source compound to form a mixture, add ethanol to ball mill, and dry at 70-90° C. to obtain a uniformly mixed powder;

[0014] S2. calcining the uniformly mixed powder in an air atmosphere to obtain a P2 / O3 dual-phase layered oxide.

[0015] Preferably, in the preparation method of the P2 / O3 dual-phase layered oxide, the sodium source compound in step S1 is one or more of sodium hydroxide, sodium oxalate, sodium acetate, sodium oxide, sodium carbonate, sodium acetate, sodium nitrate or sodium acetate, and the iron source compound is one or more of iron carbonate, ferric oxide, ferric oxide, ferric hydroxide, ferrous hydroxide or ferric acetate.

[0016] Preferably, in the method for preparing the P2 / O3 dual-phase layered oxide, in step S1, the manganese source compound is one or more of manganese oxide, manganese dioxide, manganese nitrate or manganese carbonate, and the lithium source compound is one or more of lithium oxide, lithium carbonate, lithium oxalate or lithium hydroxide.

[0017] Preferably, in the method for preparing the P2 / O3 dual-phase layered oxide, the cation A source compound in step S1 is one or more of potassium carbonate, potassium oxalate, magnesium oxide, magnesium carbonate, magnesium oxalate, calcium oxide, and calcium carbonate.

[0018] Preferably, in the method for preparing the P2 / O3 dual-phase layered oxide, in the ball milling process in step S1, the mass volume ratio of the mixture to ethanol is 1 g of the mixture mixed with 10 ml of ethanol, and the ball milling time is 8 to 20 hours.

[0019] Preferably, in the preparation method of the P2 / O3 dual-phase layered oxide, the calcination process in step S2 is: heating the uniformly mixed powder to 750-1200°C in an air atmosphere at a heating rate of 1-15°C / min, keeping the temperature for 8-25 hours, and cooling to room temperature to obtain the P2 / O3 dual-phase layered oxide.

[0020] 3. Application of the P2 / O3 dual-phase layered oxide as a positive electrode material for sodium ion batteries.

[0021] The beneficial effects of the present invention are as follows: the present invention provides a high-performance sodium ion battery layered oxide electrode material, the present invention uses A element for phase regulation, activates anion redox, maintains a relatively high initial capacity, and maintains excellent cycle performance and rate performance. It has the advantages of high capacity and long cycle life compared to the P2 phase, good rate performance of the O3 phase, and fast ion diffusion. It is not only suitable for portable electronic devices, but also can be widely used in large-scale energy storage and other fields. The material does not contain elements that are harmful to the environment, and they are all widely distributed and easy to mine elements, which greatly reduces environmental pollution and production costs.

[0022] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description.

[0023] Other advantages, objectives and features of the invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0025] Figure 1 This is the XRD spectrum of the materials shown in Comparative Example 1 and Examples 1-3;

[0026] Figure 2 This is a capacity cycle comparison diagram of the materials shown in Comparative Example 1 and Examples 1-3 (current density 150 mA / g);

[0027] Figure 3 This is a comparison chart of the rate performance of the materials shown in Comparative Example 1 and Examples 1-3 (1C = 150 mA / g);

[0028] Figure 4 is a transmission electron microscope image of the material shown in Comparative Example 1;

[0029] Figure 5 is a transmission electron microscope image of the material shown in Example 2;

[0030] Figure 6 Schematic diagram of the structural changes and cyclic stability of dual-phase materials. [] DETAILED DESCRIPTION

[0031] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0032] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.

[0033] The purity of the sodium carbonate, manganese dioxide, lithium carbonate, ferric oxide, magnesium oxide and organic solvent used in the following examples and comparative examples is not less than 98%.

[0034] Example 1

[0035] This example discloses a P2 / O3 dual-phase layered oxide Na 0.67 Li 0.1 Mg 0.05 Fe 0.35 Mn 0.5 The preparation method of O2, the specific steps are as follows:

[0036] S1. According to the molar ratio, sodium carbonate, manganese dioxide, lithium carbonate, magnesium oxide and ferric oxide are mixed evenly in a molar ratio and placed in a ball mill. Ethanol is added in a ratio of 1 g of the mixture to 10 ml of ethanol. The ball milling time is 8 to 20 hours.

[0037] Add ethanol, wet-mill in a planetary ball mill at a speed of 500 r / min for 12 h, and dry the slurry in a vacuum oven at 80° C. to obtain a precursor;

[0038] S2, after being evenly ground in an agate mortar, was transferred to an Al2O3 crucible and kept at 900℃ in an air atmosphere for 12h. After cooling, Na 0.67 Li 0.1 Mg 0.05 Fe 0.35 Mn 0.5 O2 material.

[0039] Example 2

[0040] This example discloses a P2 / O3 dual-phase layered oxide Na 0.67 Li 0.1 Mg 0.1 Fe 0.3 Mn 0.5 The preparation method of O2, the specific steps are as follows:

[0041] S1. According to the molar ratio, sodium carbonate, manganese dioxide, lithium carbonate, magnesium oxide and ferric oxide are mixed uniformly in a molar ratio and placed in a ball mill, ethanol is added in a ratio of 1 g of the mixture to 10 ml of ethanol, and wet-milled in a planetary ball mill at a speed of 500 r / min for 12 h, and the slurry is dried in a vacuum oven at 80° C. to obtain a precursor;

[0042] S2, after being evenly ground in an agate mortar, was transferred to an Al2O3 crucible and kept at 900℃ in an air atmosphere for 12h. After cooling, Na 0.67 Li 0.1 Mg 0.05 Fe 0.35 Mn 0.5 O2 material.

[0043] Example 3

[0044] This example discloses a P2 / O3 dual-phase layered oxide Na 0.67 Li 0.1 Mg 0.15 Fe 0.25 Mn 0.5 The preparation method of O2, the specific steps are as follows:

[0045] S1. According to the molar ratio, sodium carbonate, manganese dioxide, lithium carbonate, magnesium oxide and ferric oxide are mixed uniformly in a molar ratio and placed in a ball mill, ethanol is added in a ratio of 1 g of the mixture to 10 ml of ethanol, and wet-milled in a planetary ball mill at a speed of 500 r / min for 12 h, and the slurry is dried in a vacuum oven at 80° C. to obtain a precursor;

[0046] S2, after being evenly ground in an agate mortar, was transferred to an Al2O3 crucible and kept at 900℃ in an air atmosphere for 12h. After cooling, Na 0.67 Li 0.1 Mg 0.05 Fe 0.35 Mn 0.5 O2 material.

[0047] Comparative Example 1

[0048] This comparative example discloses Na 0.67 Li0.1 Fe 0.4 Mn 0.5 The preparation method of O2, the specific steps are as follows:

[0049] S1. Sodium carbonate, manganese dioxide, lithium carbonate and ferric oxide were mixed uniformly according to the molar ratio and placed in a ball mill, ethanol was added in a ratio of 1 g of the mixture to 10 ml of ethanol, and wet-milled in a planetary ball mill at a speed of 500 r / min for 12 h. The slurry was dried in a vacuum oven at 80° C. to obtain a precursor;

[0050] S2, after being evenly ground in an agate mortar, was transferred to an Al2O3 crucible and kept at 900℃ in an air atmosphere for 12h. After cooling, Na 0.67 Li 0.1 Fe 0.4 Mn 0.5 O2 material.

[0051] The materials prepared in Examples 1-3 and Comparative Example 1 were subjected to X-ray diffraction analysis to obtain the following Figure 1 Results shown.

[0052] The sodium ion battery positive electrode is prepared by:

[0053] The Na prepared in Examples 1-3 were 0.67 Li 0.1 Mg 0.05 Fe 0.35 Mn 0.5 O2 materials and Na 0.67 Li 0.1 Mg 0.1 Fe 0.3 Mn 0.5 O2 materials, Na 0.67 Li 0.1 Mg 0.15 Fe 0.25 Mn 0.5 O2 material and Na in Comparative Example 1 0.67 Li 0.1 Fe 0.4 Mn 0.5 O2 material, conductive agent acetylene black, and binder PVDF were mixed in a mass ratio of 8:1:1, and an appropriate amount of NMP solution was added. The mixture was mixed in a homogenizer, and then the slurry was evenly coated on the current collector carbon-coated aluminum foil, dried in a blast oven at 80°C for 20 minutes, and then dried at 80°C for 10 hours under vacuum conditions, and then transferred to a glove box for standby use. The battery was assembled in an argon atmosphere glove box, with a metal sodium sheet as the counter electrode and a 1M NaPF6 / PC (propylene carbonate) solution as the electrolyte, and assembled into a button cell.

[0054] The button cells using the materials of Examples 1-3 and Comparative Example 1 as the positive electrode sheets were cycled for 100 cycles at a current density of 150 mA / g. The cycle performance test results are shown in FIG. Figure 2 Shown by: Figure 2 It can be seen that the cycle performance of Examples 1-3 is significantly improved compared to Comparative Example 1.

[0055] The button cells using the materials of Examples 1-3 and Comparative Example 1 as the positive electrode were tested for rate performance at current densities of 0.2C, 0.3C, 1C, 2C, 5C, and 0.2C (1C = 150 mA / g). The test results are as follows: Figure 3 Shown by: Figure 3 It can be seen that the rate performance of Examples 1-3 is significantly improved compared to Comparative Example 1.

[0056] Then the Na prepared in Example 2 0.67 Li 0.1 Mg 0.1 Fe 0.3 Mn 0.5 O2 material and Na prepared in Comparative Example 1 0.67 Li 0.1 Fe 0.4 Mn 0.5 O2 materials were tested by transmission electron microscope imaging, and the Figure 4 and Figure 5 Detection diagram. Figure 4 and Figure 5 It shows that comparative example 1 is a single-phase material, and example 2 successfully performs phase regulation and is a P2O3 dual-phase material.

[0057] Comparative Example 2

[0058] CN 116573683 A uses solid phase calcination to prepare Na 1.2 Ni 0.26 Mn 0.67 (Zn 0.02 Nb 0.02 Fe 0.01 Co 0.01 Cu 0.01 )O2 discharge capacity at 0.1C is 157 mAh g -1 After 100 cycles, the capacity remained at about 115 mAh g -1 , the cycle retention rate is 73.2%. And the present invention maintains about 96.6% after 100 cycles.

[0059] Comparative Example 3

[0060] CN 116805684 APreparation of Na by solid phase calcination 0.796 Ni0.31 Zn 0.02 Mn 0.47 Al 0.03 Fe 0.1 Ti 0.07 The first cycle discharge capacity of O2 at 0.1C is 153.5 mAh g -1 , while the specific capacity of the present invention at 0.1C discharge is 187.83 mAh g -1 .

[0061] By comparing the above data, it can be seen that the use of element A for phase regulation can effectively combine the advantages of the P2 phase and the O3 phase to obtain a dual-phase material with excellent cycle and rate performance, high energy density and specific capacity. Figure 6 Schematic diagram of the structural changes and cyclic stability of dual-phase materials.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be covered by the scope of the claims of the present invention.

Claims

1. A P2 / O3 dual-phase layered oxide, characterized in that: The chemical formula of this oxide is Na x Fe a Mn b Li c A d O2, wherein a+b+c+d=1, 0.5<x<1.2, a+b≥0.7, 0.005≤c<0.3, 0.005≤d<0.3, and A is one or more of K, Mg and Ca elements.

2. A P2 / O3 dual-phase layered oxide according to claim 1, characterized in that: 0.6<x<0.8, 0.05≤c<0.15, 0.05≤d<0.

15.

3. A P2 / O3 dual-phase layered oxide according to claim 1, characterized in that: The oxide chemical formula is specifically Na x Fe a Mn b Li c Mg d O2.

4. A method for preparing the P2 / O3 dual-phase layered oxide according to any one of claims 1 to 3, characterized in that: The steps include: S1. Take a sodium source compound, an iron source chemical, a manganese source compound, a lithium source compound, and a cation A source compound to form a mixture, add ethanol to ball mill, and dry at 70-90° C. to obtain a uniformly mixed powder; S2. calcining the uniformly mixed powder in an air atmosphere to obtain a P2 / O3 dual-phase layered oxide.

5. The method for preparing the P2 / O3 dual-phase layered oxide according to claim 4, characterized in that: In step S1, the sodium source compound is one or more of sodium hydroxide, sodium oxalate, sodium acetate, sodium oxide, sodium carbonate, sodium acetate, sodium nitrate or sodium acetate, and the iron source compound is one or more of ferric carbonate, ferric oxide, ferric oxide, ferric hydroxide, ferrous hydroxide or ferric acetate.

6. The method for preparing the P2 / O3 dual-phase layered oxide according to claim 4, characterized in that: In step S1, the manganese source compound is one or more of manganese oxide, manganese dioxide, manganese nitrate or manganese carbonate, and the lithium source compound is one or more of lithium oxide, lithium carbonate, lithium oxalate or lithium hydroxide.

7. The method for preparing the P2 / O3 dual-phase layered oxide according to claim 4, characterized in that: In step S1, the cation A source compound is one or more of potassium carbonate, potassium oxalate, magnesium oxide, magnesium carbonate, magnesium oxalate, calcium oxide, and calcium carbonate.

8. The method for preparing the P2 / O3 dual-phase layered oxide according to claim 4, characterized in that: In the ball milling process of step S1, the mixture and ethanol are added in a ratio of 1 g of the mixture to 10 ml of ethanol, and the ball milling time is 8 to 20 hours.

9. The method for preparing the P2 / O3 dual-phase layered oxide according to claim 4, characterized in that: The calcination process in step S2 is as follows: heating the uniformly mixed powder to 750-1200° C. in an air atmosphere at a heating rate of 1-15° C. / min, keeping the temperature for 8-25 hours, and cooling to room temperature to obtain a P2 / O3 dual-phase layered oxide.

10. Application of P2 / O3 dual-phase layered oxides as positive electrode materials for sodium-ion batteries.

Citation Information

Patent Citations

  • Sodium-rich P2 / O3 biphase layered oxide and preparation method thereof, sodium ion battery positive electrode material and battery

    CN116573683A

  • Sodium-rich P2 / O3 dual-phase layered oxide and preparation method thereof, sodium ion battery positive electrode material and battery

    CN116573683B